Family veto in organ donation: the experiences of Organ and Tissue Donation Coordinators in Ontario - Anthony, Samantha J. (Can J Anaesth, 2021)
PURPOSE: In Ontario, an individual’s registered wish for organ donation is legally valid consent following death. Family veto occurs when the deceased donor’s substitute decision-maker (SDM) overrides this consent to donate, evoking a legal and ethical conflict. The objective of this study was to examine the experiences of Organ and Tissue Donation Coordinators (OTDCs) working with SDMs who vetoed a deceased donor’s consent for organ donation. METHODS: Qualitative focus groups were conducted with ten OTDCs in Ontario, Canada who reported experience with family veto. An interpretative phenomenological approach informed data analysis. Themes emerged through team consensus and were further refined through collaborative and reflexive engagement. RESULTS: Four themes emerged regarding family veto: 1) the significance of the OTDC role, 2) emotional distress and the “understandable” family veto, 3) barriers contributing to family veto, and 4) strategies towards a culture of organ donation. Findings highlighted the importance of patient advocacy in the OTDC role, while revealing the emotional distress of experiencing family veto. OTDCs identified timing and healthcare providers’ perceived ambivalence toward organ donation as critical barriers to family authorization. Value-positive language, role reframing, and increased education were offered as strategies to address these barriers and reduce family veto. CONCLUSION: This study highlights important considerations about organ donation authorization processes in Ontario. Findings support practice changes towards reducing family veto and further research nationally. Collaborations with key stakeholders are warranted to align healthcare practices, donation policies, and education initiatives towards a shared goal of increasing organ donation.